Investigating patterns of workplace fatal fall injuries: case study of Malaysia - Zermane, Abderrahim; Mohd Tohir, Mohd Zahirasri; Baharudin, Mohd Rafee; Mohamed Yusoff, Hamdan (Elsevier, 2023)
Introduction: Falling from heights can be a serious and potentially life-threatening hazard. In Malaysia, falls from heights are one of the leading causes of workplace accidents and fatalities. The Malaysian Department of Occupational Safety and Health (DOSH) reported that the year 2021 recorded an alarmingly high number of fatalities, of which the majority of the injuries were due to falls from heights. Objective: The purpose of this study is to understand the relationship between the different variables associated with fatal falls from heights, which will help identify potential areas to work on to prevent these types of injuries. Methods: The study analyzed 3,321 fatal falls from height accidents from 2010 to 2020 DOSH data. Data were cleaned and normalized to extract relevant information for analysis, with agreement on variables and reliability achieved through independent sampling. Results: This study found that general workers were the most vulnerable category to fatal falls, with a 32% yearly average, whereas supervisors were the least vulnerable, with 4%. Roofers recorded a yearly fatal falls average of 15.5%, followed by electricians with 12%. Cramer’s V results ranged from negligible, weak, and strong correlations; strong to moderate correlation between the dates of injuries and the factors used in this study, whereas the direct and root causes recorded a weak to negligible correlation with the rest of the variables. Conclusions: This study provided a better understanding of the working conditions of the Malaysian construction industry. By analyzing fall injury patterns and uncovering the factors, direct and root causes relationship with other variables, it was clear how severe the Malaysian workplace conditions were. Practical Applications: This study will help better understand fatal fall injuries in the Malaysian construction industry and help develop prevention measures based on the uncovered patterns and associations.